2003
DOI: 10.1021/jm0209376
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Inhibition Mechanism of Cyclooxygenase-2. Is There a Unique Recognition Site?

Abstract: The mechanism of binding of different nonsteroidal anti-inflammatory drugs to the cyclooxygenase active site of cyclooxygenase-2 (COX-2) has been studied by means of a wide range of theoretical techniques including molecular dynamics and free energy calculations. It is found that theoretical methods predict accurately the binding of different drugs based on different scaffolds. Calculations allow us to describe in detail the key recognition sites and to analyze how these recognition sites change depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…The amide hydrogens of the sulphonamide group interact with the backbone of Phe518 via two water bridges. Unfortunately, x-rays have not been able to resolve the conformation of the sulphonamide group in the selectivity pocket, and conformations dissimilar to the x-rays' one have been already reported in previous theoretical studies (25,26).…”
Section: Resultsmentioning
confidence: 94%
“…The amide hydrogens of the sulphonamide group interact with the backbone of Phe518 via two water bridges. Unfortunately, x-rays have not been able to resolve the conformation of the sulphonamide group in the selectivity pocket, and conformations dissimilar to the x-rays' one have been already reported in previous theoretical studies (25,26).…”
Section: Resultsmentioning
confidence: 94%
“…Robert et al demonstrated the binding mechanism of diferent NSAIDs (mainly celecoxib and rofecoxib analogues) to the cyclooxygenase active site of COX-2 based on molecular dynamics (MD) simulation and free energy calculation studies [37]. The MD simulation study carried out by using the homology model of human COX-2 also revealed similar binding mode of interaction of SC-558 as observed from crystallographic pose [33].…”
Section: Molecular Basis Of Inhibition Of Cyclooxygenase Enzymes and mentioning
confidence: 86%
“…To investigate the key residues involved in the interaction of NSAIDs with COX-2, the MD trajectories were analysed by using UBEXTRACT programme. For example, the UBEXTRACT analysis [37] indicated that mainly four residues (Arg120, Asn192, Leu352 and Arg513) made signiicant electrostatic interactions, whereas thirteen residues involved in van der Waals interaction with the SC-558 ( Figure 4B). The inspection of experimental data of valdecoxib suggested that the methyl group atached to the central isoxazole ring is favourable for binding by making hydrophobic interaction.…”
Section: Molecular Basis Of Inhibition Of Cyclooxygenase Enzymes and mentioning
confidence: 99%
See 1 more Smart Citation
“…The 6COX structure was chosen over 1CX2 (the same complex crystallized in a different space group) because it contains the correct conformation of the sulfonamide group relative to the connected aromatic ring, as demonstrated by simulation studies. 23,24 Structural manipulation was done in SYBYL 6.9 (Tripos, St. Louis, MO).…”
Section: Structure Preparationmentioning
confidence: 99%